AWARENESS OF MENSTRUAL HYGIENE AMONG ADOLESCENT GIRLS AT A GOVERNMENT SCHOOL, CHITWAN, NEPAL - Bajracharya, Subina; Baniya, Ambika (Journal of Chitwan Medical College, 2022)
Background: Adolescence is a transition period from childhood to adult life during which pubertal development and sexual maturation take place. Menstrual hygiene and management is an issue that is insufficiently acknowledged and has not received adequate attention. Good menstrual hygiene is crucial for health, education and dignity of adolescent girls. The objective of this study was to assess the awareness and practice regarding menstrual hygiene among adolescent girls. Methods: A cross-sectional study was conducted to assess the awareness regarding menstrual hygiene among 150 adolescent girls aged 12-17 years studying in grades 9 and 10 of a government school, Chitwan. Purposive sampling technique was used to select the sample. Data were collected using structured self-administered questionnaires and analyzed by using descriptive and inferential statistics. Results: Majority of the respondents were 12-14 years old with the mean age of menarche at 12.5± 1.14 years, 52% of respondents had adequate knowledge and 61.3% of them had good practice on menstrual hygiene. Statistically significant association was found between level of practice and mother’s education status (p<0.05). Correlation between knowledge and practice score was poorly positive (r-0.087) but statistically insignificant (p>0.05). Conclusions: Majority of respondents had adequate knowledge and adequate practice on menstrual hygiene. For the maintenance of good reproductive health girl child should be made more aware about menstrual health and hygiene through the campaign and education programs.